Surya - Temples of India Project Team (Jio Institute, 2024)
Standing male deity in the samabhanga pose adorned with a mukuta (headgear), meshed armour, uttariya (stole or scarf-like garment) and boots. He holds lotuses in full bloom in both hands. Broken figures of Danda and Pingala are present on either side of the legs.